Francisco Adolfo de Varnhagen and some key guidelines to the Portuguese historiography of his time (1839-1841) - Protásio, Daniel Estudante (2013)
With the present article, I intend to contribute to the study of Francisco Adolfo de Varnhagen’s relations with the Portuguese historiographical community, and also to emphasize his personal and intellectual proximity and distance to some of the most relevant names of the Portuguese historiography of the period, such as Cardinal Saraiva, Alexandre Herculano, and the Viscount of Santarem. The study was based on manuscript sources and on Portuguese and Brazilian bibliography. The letter that the Viscount of Santarem wrote to Varnhagen, dated December 8, 1839, is frequently cited as having used, for the first time, the word cartography, which is credited to Santarem. The letter was written during a dispute between the two authors, about some of the characteristics of the cultural studies dedicated to the Portuguese history, both in Paris and Lisbon, and, more importantly, about the work Crónica da Guiné, by Zurara, and the importance of the undiscovered document’s relevance as an instrument of affirmation and prestige for the historian.